Erratum: Effectiveness of Long-Acting Injectable Antipsychotics in Schizophrenia: A Literature Review and Bayesian Meta-Analysis Informing Economic Considerations - listed], [No authors (Farmeconomia. Health Economics and Therapeutic Pathways, 2019)
There was an error in the relapse rate reduction reported in Figure 2 in this article by Zaniolo et al. [Farmeconomia. Health economics and therapeutic pathways 2019; 20: 13-24; https://doi.org/10.7175/fe.v20i1.1393]. The online version has been corrected on 13 February 2019.